Adaptation of Stadier’s apparatus for electrophoresis of main milk proteins - Yukalo, Volodymy; Datsyshyn, Kateryna; Krupa, Olha; Storozh, Liudmyla (Eastern-European Journal of Enterprise Technologies, 2024)
The object of research is a Stadier-type apparatus for analytical electrophoresis of proteins. In the milk proteins research, in addition, there is a need to carry out serial express analyzes of their various groups, as well as the isolation of individual homogeneous fractions. The dimensions of working chambers for analytical, express, and micro preparative electrophoresis of caseins and milk whey proteins were proposed to solve this task. For each type of electrophoresis, different chambers and formers are used without changing the design of the apparatus. The apparatus is suitable for electrophoretic systems used for the analysis of milk proteins. Analysis of casein in the anodic system of a homogeneous polyacrylamide gel in the presence of urea allows identification of the main fractions: αS1-CN-8P, αS1-CN-9P, αS2-CN-10P, αS2-CN-11P, αS2-CN-12P, αS2-CN-13P, β-CN-5P, ϰ-CN-1P and three β-casein fragments f(29-209), f(106-209) and f(108-209). Express electrophoresis in the presence of urea reveals four fractions of caseins: αS1-CN, αS2-CN, β-CN, and ϰ-CN. The analysis of whey proteins in the Davis native disc electrophoresis system allows identification of β-Lg A, β-Lg B, α-La, BSA fractions, and a group of immunoglobulin fractions. The express electrophoregram differs by a common band A and B variants of β-Lg. Due to an adequate selection of electrophoretic systems, it is possible to identify semi-quantitatively all the main fractions of milk proteins under analytical or express mode. The adapted apparatus also makes it possible to conduct micro preparative electrophoresis and obtain the main fractions of milk proteins. In this case, the yield of electrophoretically pure proteins is: β-CN-5P (23±5 %), β-Lg (A+B) (27±6 %), α-La (11±3 %), and purified groups of αS1-CN-8P+αS1-CN-9P (25±6 %), αS2-CN-(10-13P) (6±1.5 %) and ϰ-CN-1P (7±2 %). The apparatus could be used at enterprises producing dairy protein products